2019
DOI: 10.1177/1527002519859416
|View full text |Cite
|
Sign up to set email alerts
|

Universities Behaving Badly: The Impact of Athletic Malfeasance on Student Quality and Enrollment

Abstract: National accolades and positive media attention are frequently lavished upon successful collegiate sports programs. Correspondingly, studies have demonstrated that universities often benefit from the achievements of their athletic teams by increasing the schools’ application numbers, student quality, and alumni donations. This study demonstrates that the opposite effect occurs when a university’s sports team is accused of engaging in impropriety. Our findings suggest that the negative attention given to the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We find, by contrast, that unexpected, Cinderella basketball performances increase yield (the percent of admitted freshmen who choose to enroll) for private universities, which tend to be smaller and less well-known. The effect on enrollment from unexpected March Madness success is akin to the decline in enrollment following athletic team impropriety (and likely subsequent sanctions; Eggers et al, 2019Eggers et al, , 2020. Taken together, perhaps potential students respond to advertising from expected athletic success in applications, while unexpected changes to athletic team status affects enrollment decisions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We find, by contrast, that unexpected, Cinderella basketball performances increase yield (the percent of admitted freshmen who choose to enroll) for private universities, which tend to be smaller and less well-known. The effect on enrollment from unexpected March Madness success is akin to the decline in enrollment following athletic team impropriety (and likely subsequent sanctions; Eggers et al, 2019Eggers et al, , 2020. Taken together, perhaps potential students respond to advertising from expected athletic success in applications, while unexpected changes to athletic team status affects enrollment decisions.…”
Section: Resultsmentioning
confidence: 99%
“…Academic studies have also found lower grades can result from participation in athletics and from fielding successful athletic teams (Hernández-Julián & Rotthoff, 2014;Lindo et al, 2012;Maloney & McCormick, 1993). Additionally, when a school has an athletic team that engages in impropriety, it can lead to lower enrollments and quality of incoming students (Eggers et al, 2019(Eggers et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…As such, college athletic programs are inextricably linked to school branding and reputation. Further, college athletics have been found to play an integral role in student enrollment and increase college / university profiles (Goff, 2000;Eggers, Groothuis, Redding, Rotthoff, & Solimini, 2020). This in turn often results in financial windfalls in the form of corporate partnerships and donations that ultimately contribute to the financial solvency of the institutions.…”
Section: College Athletics: Coin Of the Realmmentioning
confidence: 99%
“…Sanctions can affect the competitive balance in sports (Depkin & Wilson, 2006) and employment and promotion decisions about coaches (Soebbing et al, 2015). Eggers et al (2020) and Groothuis et al (2019) find that postseason bans on collegiate level basketball teams negatively affect the quality and quantity of applications to the college or university, and these results persist for years after the ban is lifted. Johnson and McCannon (2019) also look at the quality of the incoming freshman classes at Penn State University after the football scandal in 2011.…”
Section: Related Literaturementioning
confidence: 99%
“…Misconduct, athletic or otherwise, can hurt a school financially or in academic performance. Eggers et al (2020) and Groothuis et al (2019) show that sanctions on NCAA basketball programs have adverse effects on academic outcomes, such as the number of applications and the quality of those applicants. Rooney and Smith (2019) find that high-profile instances of misconduct, not just athletic ones, at universities negatively affect the number of applicants in the following year.…”
Section: Introductionmentioning
confidence: 99%